Initiative for Excellence: Great Expectations, Scaled Back (KULT_online, 2010)
Die Illusion der Exzellenz (The Illusion of Excellence), a collection of essays edited by FAZ journalist Jürgen Kaube, discusses the recent reforms in German higher education and thus exposes the façade of German higher education policy. According to the authors’ views, the promises inherent in the reforms have not been honored. These shortcomings are examined from various angles stemming from both the social and natural sciences. Although the authors’ personal experiences and critical examinations might add some fuel to the fire of ongoing debate on the Bologna process and the Excellence Initiative, the volume ultimately fails to explain the current dynamics of the situation at universities and in higher education policy.